2018
DOI: 10.1108/jes-08-2016-0162
|View full text |Cite
|
Sign up to set email alerts
|

Households’ financial vulnerability in Southern Europe

Abstract: Purpose The purpose of this paper is to analyze whether and to what extent households living in southern Europe, i.e. Greece, Portugal, Spain and Italy, experience similar conditions of financial vulnerability, considering that in comparative research these countries are often grouped together because of the substantial instability of their economies and the similarity of social and welfare model. Design/methodology/approach The authors use data from Household Finance and Consumption Survey, a quite novel da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Ba nbuła et al (2015) found that households with a debtservice-to-income ratio of more than a threshold value of 40% are vulnerable. Terraneo (2018), Household financial vulnerability in India in the context of Southern Europe, had highlighted four objective indicators of debt burden, that is, debt-to-asset ratio (DAR), debt-to-income ratio (DIR), debt-service-to-income ratio (DSIR) and mortgage debt service-to-income ratio (MDSIR). Though debt is an important indicator of financial vulnerability, it should not be taken as a sole measure.…”
Section: Literature Review 21 Financial Vulnerability Conceptmentioning
confidence: 99%
“…Ba nbuła et al (2015) found that households with a debtservice-to-income ratio of more than a threshold value of 40% are vulnerable. Terraneo (2018), Household financial vulnerability in India in the context of Southern Europe, had highlighted four objective indicators of debt burden, that is, debt-to-asset ratio (DAR), debt-to-income ratio (DIR), debt-service-to-income ratio (DSIR) and mortgage debt service-to-income ratio (MDSIR). Though debt is an important indicator of financial vulnerability, it should not be taken as a sole measure.…”
Section: Literature Review 21 Financial Vulnerability Conceptmentioning
confidence: 99%
“…Among the measures listed above, debt-service to income ratio (DSTI) seems the most relevant indicator. Most studies put the limit at 30% or 40% of debt-service to income (Tiongson et al 2009;Michelangeli and Pietrunti 2014;Sánchez-Martínez et al 2016;D'Alessio and Iezzi 2016;Terraneo 2018). In countries with the well-developed credit markets (e.g.…”
Section: Definition and Measurement Of Over-indebtednessmentioning
confidence: 99%
“…Education and income were treated as instruments. The choice of instruments was influenced by the related literature (e.g., Daud et al, 2019;Abid and Shaifai, 2018;Terraneo, 2018). Sargan over-identification test served to test the validity of instruments (Null hypothesis: all instruments are valid).…”
Section: Data Sources and Methodologymentioning
confidence: 99%